Removing a broken guidewire in the hip joint: treatment options and recommendations for preventing an avoidable surgical catastrophe. A case report - Salunke, Abhijeet Ashok (2015)
CONTEXT: Hardware breakage during hip surgery can pose challenging and difficult problems for orthopedic surgeons. Apart from technical difficulties relating to retrieval of the broken hardware, complications such as adjacent joint arthritis and damage to neurovascular structures and major viscera can occur. Complications occurring during the perioperative period must be informed to the patient and proper documentation is essential. The treatment options must be discussed with the patient and relatives and the implant company must be informed about this untoward incident. CASE REPORT: We report a case of complete removal of the implant and then removal of the broken guidewire using a combination of techniques, including a cannulated drill bit, pituitary forceps and Kerrison rongeur. CONCLUSIONS: We suggest some treatment options and recommendations for preventing an avoidable surgical catastrophe.